2019
DOI: 10.2174/1871527317666180816095707
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise and Ferulic Acid on Alpha Synuclein and Neuroprotective Heat Shock Protein 70 in An Experimental Model of Parkinsonism Disease

Abstract: FR and Ex seems to improve the motor performance in PD rodent model which might be due to upregulation of Hsp70 and increasing density of dopaminergic neurons in corpus striatum. FR offers more protective effects than Ex and combination of both did not offer more protection than FR alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Interestingly, ferulic acid and exercise seem to improve the motor performance in a PD rodent model which might be due to the upregulation of Hsp70 and increasing density of dopaminergic neurons in the corpus striatum. Ferulic acid offers more protective effects than exercise and combination of both did not offer more protection than ferulic acid alone [127].…”
Section: Targeting Dopaminergic Neurons Cytotoxicitymentioning
confidence: 86%
“…Interestingly, ferulic acid and exercise seem to improve the motor performance in a PD rodent model which might be due to the upregulation of Hsp70 and increasing density of dopaminergic neurons in the corpus striatum. Ferulic acid offers more protective effects than exercise and combination of both did not offer more protection than ferulic acid alone [127].…”
Section: Targeting Dopaminergic Neurons Cytotoxicitymentioning
confidence: 86%
“…FA also reduced mitochondrial expression of Drp1 and increased expression of the PGC1α gene and protein, thereby regulating expression of its downstream target Mfn2 and restoring mitochondrial dynamics in 6-OHDA-lesioned PD animal models [171]. Hence, the combination of FA and muscle exercise effectively improved motor function and increased HSP-70 expression and TH-positive fibers in the corpus ST in rotenone-induced PD mice [172].…”
Section: Neuroprotective Mechanisms Of Asiatic Acid In Pdmentioning
confidence: 94%
“…Many studies reported promising results toward effective management of cognitive and non-motor functions (Balakrishnan et al, 2021). However, compounds such as BBR, quercetin, ferulic acid (FA), etc., have also shown promising motor functions in neuro-disorder induced rat and mice models (Chen et al, 2002;Van Kampen et al, 2003;Zhao et al, 2008;Kim et al, 2014;Jiang et al, 2015;Yadav et al, 2016;Askar et al, 2019;Madiha et al, 2021). For example, blueberry supplementation (rich in polyphenols) in the geriatric population effectively checks the decline of functional mobility and improves the performance of activities of daily living (Schrager et al, 2015).…”
Section: Phytochemicals and Its Neuroprotective Rolesmentioning
confidence: 99%